2020
DOI: 10.1038/s41416-020-0766-1
|View full text |Cite
|
Sign up to set email alerts
|

Correction: A multicentre, prospective study of plasma circulating tumour DNA test for detecting RAS mutation in patients with metastatic colorectal cancer

Abstract: An amendment to this paper has been published and can be accessed via a link at the top of the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“… 45 GO enrichment and KEGG pathway analyses further revealed that the hub lncRNAs were involved in the RAS signaling pathway and transcriptional activator activity, as reported in previous studies. 46–48 In vivo and in vitro assays were conducted to verify if overexpression of LINC00909 could enhance NCRT resistance in CRC, and were consistent with the microarray and qPCR results.…”
Section: Discussionmentioning
confidence: 57%
“… 45 GO enrichment and KEGG pathway analyses further revealed that the hub lncRNAs were involved in the RAS signaling pathway and transcriptional activator activity, as reported in previous studies. 46–48 In vivo and in vitro assays were conducted to verify if overexpression of LINC00909 could enhance NCRT resistance in CRC, and were consistent with the microarray and qPCR results.…”
Section: Discussionmentioning
confidence: 57%
“…The ceRNA network was constructed based on the hypothesis that lncRNAs directly interact with miRNAs and regulate the activity of mRNAs by acting as miRNA sponges [41]. Based on the associated mRNA, the GO enrichment and KEGG analysis were performed, the results demonstrated that the hub lncRNAs involve in the RAS signaling pathway and transcriptional activator activity, which had been reported in the previous studies [42][43][44]. Moreover, we successfully constructed the LINC00909 overexpression CRC cell lines to veri ed that overexpression LINC00909 could enhance the resistance to the NCRT in CRC.…”
Section: Discussionmentioning
confidence: 68%
“…Tumors from the brain, renal, and thyroid have repeatedly been observed to have a lower ctDNA detection compared to colorectal, lung, and breast cancer, even at an advanced stage [40,125]. Furthermore, several studies have also reported that the detection rate of ctDNA is significantly higher in colorectal cancer patients with liver metastasis compared to nodal or lung metastasis [128][129][130]. The performance of ctDNA NGS assays was found to be highly dependent on the ctDNA fraction, particularly for detecting gene amplification [42,58,131].…”
Section: Biological Limitations: Low Tumor Shedding and Non-tumoral O...mentioning
confidence: 99%